CHO-S Antibody Titers >1 Gram/Liter Using Flow Electroporation-Mediated Transient Gene Expression followed by Rapid Migration to High-Yield Stable Cell Lines. (April 2015) - Steger, Krista; Brady, James; Wang, Weili; Duskin, Meg; Donato, Karen; Peshwa, Madhusudan
In recent years, researchers have turned to transient gene expression (TGE) as an alternative to CHO stable cell line generation for early-stage antibody development. Despite advances in transfection methods and culture optimization, the majority of CHO-based TGE systems produce insufficient antibody titers for extensive use within biotherapeutic development pipelines. Flow electroporation using the MaxCyte STX Scalable Transfection System is a highly efficient, scalable means of CHO-based TGE for gram-level production of antibodies without the need for specialized expression vectors or genetically engineered CHO cell lines. CHO cell flow electroporation is easily scaled from milligram to multigram quantities without protocol reoptimization while maintaining transfection performance and antibody productivity. In this article, data are presented that demonstrate the reproducibility, scalability, and antibody production capabilities of CHO-based TGE using the MaxCyte STX. Data show optimization of posttransfection parameters such as cell density, media composition, and feed strategy that result in secreted antibody titers >1 g/L and production of multiple grams of antibody within 2 weeks of a single CHO-S cell transfection. In addition, data are presented to demonstrate the application of scalable electroporation for the rapid generation of high-yield stable CHO cell lines to bridge the gap between early- and late-stage antibody development activities.